Epidemiology and risk factors of nasal carriage of Staphylococcus aureus CC398 in two distinct cohorts in France - Bouiller, Kevin; Zeggay, Abdeljalil; Gbaguidi-Haore, Houssein; Hocquet, Didier; Chirouze, Catherine; Bertrand, Xavier (Frontiers in Microbiology, 2022)
Background We aimed to determine the prevalence and factors associated with nasal carriage of Staphylococcus aureus CC398 in the community and among hospitalized patients. Methods We conducted a prospective cohort study in a French university hospital and a cross-sectional study in the surrounding region. Results From June 2019 to July 2020, 591 healthy blood donors (HBDs) and 647 hospitalized patients (HPs) were included. S. aureus CC398 was more prevalent in HBDs than in HPs (7.3% [5.3–9.7] vs. 3.8% [2.4–5.5], p = 0.006). Among S. aureus nasal carriers, the prevalence of CC398 isolates was 24.6% in HBDs and 18.3% in HPs (p = 0.19). No MRSA belonged to CC398. In multivariate analysis, prior antibiotic intake in the past year (OR 3.11 [1.37–7.06]) and active smoking (OR 3.01 [1.00–9.05]) were associated with S. aureus CC398 nasal carriage in the HBD cohort. A history of neurological disease was associated with nasal carriage (OR = 5.43 [1.21–24.2]), whereas an age between 82 and 90 years (OR 0.11 [0.02–0.54]) and diabetes (OR 0.18 [0.04–0.85]) were protective factors in the HP cohort. Contact with livestock was not a risk factor in either cohort. Conclusion The prevalence of MSSA CC398 was higher in the community than hospitalized patients. Factors associated with nasal carriage of MSSA CC398 were primarily related to general preconditions. No environmental sources of exposure were identified.